Pengaruh Model Problem Based Learning terhadap Keterampilan Menulis Teks Eksposisi dari Siswa Sekolah Menengah - Efrianto Efrianto; Siska Novelia; Afnita Afnita (Lingua Susastra, 2020)
The purpose of this study was to discuss the effect of the Problem Based Learning (PBL) model on writing skills of exposition text for middle school students. The method used is an experiment inquiry to find the effect of certain treatments on others under controlled conditions. The research procedure which is natural setting and descriptive pay more attention to data processing and analysis, tend to be inductive, and search for suitable meaning. The data collection instrument was a performance test in the form of writing skills on exposition text. The results showed that the application of the PBL model increased the scores of the students' exposition text writing results with an average score of 58%. In addition, the application of the PBL model also deepens students' understanding of the structure, language rules, diction, language style, and speeling contained in the exposition text.